2019
DOI: 10.1002/app.47840
|View full text |Cite
|
Sign up to set email alerts
|

The effect of iron oxide nanoparticles on the mechanical relaxation of magnetic polymer hybrid films composed of a polystyrene matrix, a fractional calculus approach

Abstract: A magnetic polymer hybrid film (MPHF) with a thickness of ~80 μm, composed of iron oxide nanoparticles (IONPs) in a polystyrene (PS) matrix, was successfully prepared. Its structure and morphology were analyzed by HRTEM, XRD, and FTIR. The optical and magnetic behaviors were studied by UV–Vis spectroscopy and VSM, respectively. The main relaxation of the MPHF was characterized by dynamic mechanical analysis (DMA), and the molecular mobility was analyzed by a fractional Zener model (FZM). Results obtained by DM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 40 publications
1
5
0
Order By: Relevance
“…The composite copolymer (PMNC4) also shows this peak with two additional weak absorption peaks due to IONs present in the composite. In Figure 2C these are observed at around 360 nm due to the direct electronic transition from 2p orbital of O 2 − anion to 3d orbital of Fe 3+ and in the visible range in between 400 and 500 nm due to indirect 3d–3d charge transfer as reported elsewhere 33 . It is also observed that with the increase in the mol% of 4VP in the following order PMNC9(6.2%) < PMNC2 (9.1%) < PMNC4 (16.7%) as also shown in Table 1, the intensity of the absorption peaks due to IONs also increases.…”
Section: Resultssupporting
confidence: 80%
See 2 more Smart Citations
“…The composite copolymer (PMNC4) also shows this peak with two additional weak absorption peaks due to IONs present in the composite. In Figure 2C these are observed at around 360 nm due to the direct electronic transition from 2p orbital of O 2 − anion to 3d orbital of Fe 3+ and in the visible range in between 400 and 500 nm due to indirect 3d–3d charge transfer as reported elsewhere 33 . It is also observed that with the increase in the mol% of 4VP in the following order PMNC9(6.2%) < PMNC2 (9.1%) < PMNC4 (16.7%) as also shown in Table 1, the intensity of the absorption peaks due to IONs also increases.…”
Section: Resultssupporting
confidence: 80%
“…In Figure 2C these are observed at around 360 nm due to the direct electronic transition from 2p orbital of O 2 À anion to 3d orbital of Fe 3+ and in the visible range in between 400 and 500 nm due to indirect 3d-3d charge transfer as reported elsewhere. 33 It is also observed that with the increase in the mol% of 4VP in the following order PMNC9(6.2%) < PMNC2 (9.1%) < PMNC4 (16.7%) as also shown in Table 1, the intensity of the absorption peaks due to IONs also increases. In fact, the pyridine moiety promotes the formation and entrapment of ION in the copolymer by hydrogen bonding interaction and complexation reaction.…”
Section: Ftir Proton and 13c Nmr Uv-vis Absorptionmentioning
confidence: 54%
See 1 more Smart Citation
“…This is because these applications are useful characteristics of low cost, lightweight, ease of manufacture, versatility, thermal efficiency, durability, low distortion, and moisture resistance 9 . Besides, from an electrical point of view, polystyrene films provide high insulation, low leakage, low dielectric absorption, and excellent temperature stability 10,11 . From a scientific point of view, Perov proposed to use PS films for the study of polymer relaxation phenomena 12 .…”
Section: Introductionmentioning
confidence: 99%
“…To obtain a rheological model capable of describing experimental results, the classical Zener model is modified with two springpots to obtain the so-called Fractional Zener Model or FZM (see Figure 2 ). It has been reported that the fractional order parameters of the FZM are related to the cooperative molecular mobility of the mechanical relaxation phenomena in polymers [ 19 , 24 , 25 ]. Puente-Córdova et al [ 26 ] reported the use of the FZM to model the viscoelastic behavior of isotropic and anisotropic magnetorheological elastomers.…”
Section: Methodsmentioning
confidence: 99%